Coping professionally with closeness: Caught between children's needs and self-protection - Meike Wittfeld (Social Work and Society)
In residential child and youth care, situations and constellations that bring professionals and residents close to each other are an everyday occurrence. Even just the spatial setup and the structural dependencies force individual persons to interact with each other both physically and emotionally. They are involved with each other affectively and dependent on each other. Educational science and pedagogics have analysed how situations and constellations of physical and emotional closeness should be organized professionally. The first part of this article highlights some of these pedagogic perspectives on how to deal with situations of closeness, emotional involvement, and professional distance. The second part presents selected results of a qualitative study from Germany based on group discussions with staff of residential youth care homes reconstructed strategies of coping with necessary closeness between caregivers and children (cf. Bohnsack, 2010). The results show, that against the background of the public discourse about sexual violence in child and youth care institutions, professionals struggle to find appropriate strategies of balancing the pedagogic antinomy of closeness and distance (cf. Helsper, 2006). The third and final part of the article integrates the theoretical and empirical results and concludes that the media and public attention concerning sexual violence in institutions reinforces the tension professionals feel between children's needs and self-protection.